Nilai-Nilai Moral dalam novel Pulang karya Leila S. Chudori - Rahmadhani, Ridha Suci; Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to describe the moral values regarding human bonds with God, individual relationships with themselves, individual relationships with other individuals in a social sphere in a novel entitled Pulang. The type of this research is literary research using the content analysis method. The data source in this research is the novel Pulang by Leila S. Chudori. Data collection techniques in this study were carried out by reading, marking events and inventorying the data found. Data analysis techniques include data classification, data analysis, and conclusion drawing. The results of this study show that human relationships with God consist of tawakal, gratitude, and prayer. Furthermore, human relationships with themselves consist of firmness, regret, and optimism. Third, human relationships with other humans in the social sphere consisting of caring for others, being grateful, honest, and respecting others. This study concludes that Pulang's novel is rich in moral values that can be exemplified by readers. These moral values can help readers build harmonious relationships with God, themselves, and others.